Molecular detection of Epstein Barr Virus in Women with Breast cancer - Hussein, Areej A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Epstein Barr Virus (EBV) infection has been implicated in pathogenesis of several types of carcinomas such as nasopharyngeal carcinoma, gastric cancer and bladder cancer and has recently been associated with breast cancer.Objective: To evaluate the relations between Epstein Barr virus-encoded small RNA (EBER) and breast cancer.Methods: Twenty two cases of breast cancer were retrieved from the Al-Kadhimiya Teaching Hospital in Baghdad. Clinical data were analyzed from the medical records and formalin fixed, paraffin embedded tumor tissue were examined by Chromogeneic in situ hybridization (ISH) technique for the detection of EBER.Results: The expression of EBER in tissues patients with breast cancer in the present study was 50% (11out of 22), where strong correlation was found between expression of EBER and patients with breast cancer. While not found significant differences between ISH expressions of EBER with age, type of cancer, grade and lymph node metastasis.Conclusion: Based on the results of the current study, Epstein Barr virus infection plays a major role in the pathogenesis of breast cancer.